Development of Physics Demonstration Videos on Youtube (PDVY) as Physics Learning Media - Irvani, A I; Warliani, R (Department of Physics, Faculty of Mathematics and Natural Sciences, 2022)
The availability of physics demonstration videos relevant to curriculum needs is still limited. The aims of this study were (1) to develop physics learning media in the form of demonstration videos; (2) testing the feasibility of using demonstration videos as a medium for learning physics; and (3) knowing student responses to demonstration videos. The name of this demonstration video is Physics Demonstration Videos on YouTube (PDVY). This video is available on the PDVY Indonesia YouTube channel with open access. This research uses research and development methods. The steps for making this demonstration video consist of analyzing the core standards and competency standards of physics subjects, designing storyboards, taking pictures, editing, initial testing, revising initial test results, field trials and revising the results of field trials. The trial was conducted on 129 high school students in Garut, Indonesia. The results showed that (1) the physics demonstration video was composed with input from the validator, two physics lecturers, and two physics teachers; (2) the demonstration video is suitable for use as a physics learning medium from the material and media aspects; and (3) excellent response from high school students and teachers. Based on the validation of both the content validator and the media validator, it shows that the design of the parabolic motion demonstration video is very valid. The benefit aspect gets the highest score. This shows that the video developed has a high use value in the learning process.